2023
DOI: 10.1021/acs.analchem.3c00717
|View full text |Cite
|
Sign up to set email alerts
|

FRET-Based Single-Molecule Detection of Pathogen Protein IsdA Using Computationally Selected Aptamers

Kalani M. Wijesinghe,
Godfred Sabbih,
Chamika Harshani Algama
et al.

Abstract: Iron-regulated surface determinant protein A (IsdA) is a key surface protein found in the foodborne bacteriaStaphylococcus aureus (S. aureus)which is known to be critical for bacterial survival and colonization. S. aureus is pathogenic and has been linked to foodborne diseases; thus, early detection is critical to prevent diseases caused by this bacterium. Despite IsdA being a specific marker for S. aureus and several detection methods have been developed for sensitive detection of this bacteria such as cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…For instance, RNA aptamers have been reported that target teichoic acid in S. aureus [53], a component of the cell wall of most Gram-positive bacteria, as well as peptidoglycan-specific aptamers for the detection of S. aureus and E. coli [54] and, more recently, aptamers targeting isdA, a crucial surface protein for S. aureus' survival and colonization. Over time, this protein has gradually become a key marker for the detection of this bacterium [55,56].…”
Section: Aptamer Selection Strategies For Bacterial Pathogen Detectionmentioning
confidence: 99%
“…For instance, RNA aptamers have been reported that target teichoic acid in S. aureus [53], a component of the cell wall of most Gram-positive bacteria, as well as peptidoglycan-specific aptamers for the detection of S. aureus and E. coli [54] and, more recently, aptamers targeting isdA, a crucial surface protein for S. aureus' survival and colonization. Over time, this protein has gradually become a key marker for the detection of this bacterium [55,56].…”
Section: Aptamer Selection Strategies For Bacterial Pathogen Detectionmentioning
confidence: 99%
“…More recently, aptamers that specifically target isdA, a crucial surface protein for S. aureus survival and colonization, have been successfully generated. Over time, this protein is gradually becoming a key marker for the detection of this bacterium [49,50].…”
Section: Aptamer Selection Strategies For Bacterial Pathogen Detectionmentioning
confidence: 99%